2020
DOI: 10.1002/ajmg.a.61551
|View full text |Cite
|
Sign up to set email alerts
|

The clinical overlap between cardiac‐urogenital syndrome, Meacham syndrome, and PAGOD syndrome. Report of a new patient with cardiac‐urogenital syndrome

Abstract: We have read with great interest the article "Review of the phenotypic spectrum associated with haploinsufficiency of MYRF" by Rossetti et al. published in The American Journal of Medical Genetics (2019;179A: 1376-1382) (Rossetti et al., 2019). We want to congratulate the authors on their review and make some contributions. We report a de novo novel pathogenic variant on the MYRF gene consistent with the reported phenotype of cardiac-urogenital syndrome and reflect on phenotypical similarities between this new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…He was further described to have cognitive impairment with an intelligence quotient score of 20. At 4 years of age, brain magnetic resonance imaging showed signs of delayed myelination (Alves & Leão, 2020). The patient's neurological impairment was reported as well by Pinz et al, who described one patient with speech delay who lived until 18 months, and Qi et al, who reported a 2‐year‐old with intellectual disability and motor delay (Pinz et al, 2018; Qi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…He was further described to have cognitive impairment with an intelligence quotient score of 20. At 4 years of age, brain magnetic resonance imaging showed signs of delayed myelination (Alves & Leão, 2020). The patient's neurological impairment was reported as well by Pinz et al, who described one patient with speech delay who lived until 18 months, and Qi et al, who reported a 2‐year‐old with intellectual disability and motor delay (Pinz et al, 2018; Qi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[7,[34][35][36]41,42] Additionally, it presents with a wide spectrum of developmental delay and intellectual disability, pulmonary abnormalities, diaphragmatic issues, and intestinal malrotation. [41,[43][44][45][46][47][48] Many aspects of these developmental processes remain incompletely understood, and the causes of abnormal development are not well-established. A pathogenic variant of MYRF is also associated with neurological conditions characterized by extensive myelin vacuolization, reflecting similar findings observed in mice where Myrf plays a crucial role in regulating myelination.…”
Section: Humansmentioning
confidence: 99%
“…DD and ID encompass a broad spectrum of conditions, ranging from mild speech delays to severe developmental delays and cognitive impairment. [7,41,43] The severity and prevalence of these conditions can be influenced by the presence of cardiopulmonary defects.…”
Section: Developmental Delay (Dd) and Intellectual Disability (Id)mentioning
confidence: 99%
See 2 more Smart Citations